Acoustic Effects of the Singing Voice Quality of Untrained Female Singers in Malaysia. - Wei Shean Ter; Kwan Yie Wong (Wacana Seni Journal of Arts Discourse, 2022)
Vocal warm-ups are widespread and comprehensive in the singing community. Although it is well recognised and practised by professionals, warm-ups are sometimes bypassed and neglected by singers and voice teachers. The objective of this study is to assess the impact of vocal warm-up on vocal quality through acoustic parameters of jitter (%), shimmer (%), and harmonics-to-noise (HNR [dB]) in two-pitch conditions, A3 (chest register) and C5 (head register), before and after vocal warm-up. Forty untrained female singers were recorded twice while uttering the vowels/a/,/o/, and/i/in two different pitches: Low--A3 (220.0 Hz) and High--C5 (523.2 Hz) for at least five seconds. A standardised warm-up protocol with a duration of 20-minute was carried out in this study. The subjects were recorded immediately before and after a 20-minute vocal warm-up session. Significant improvements were found in the mean values of measured acoustic parameters. A decrease was observed compared with the mean jitter and shimmer values before and after a vocal warm-up, while the HNR increased. All the acoustic variables, jitter, shimmer, and HNR were found to have significantly larger improvements in the lower pitch, A3 (chest register), compared to the higher pitch, C5 (head register). The findings of this study provided empirical evidence for the beneficial effect of vocal warm-up on the voice quality of untrained female singers. The positive effects of the findings indicated that the vocal warm-up should be encouraged and not bypassed.